2018
DOI: 10.18203/2320-1770.ijrcog20180175
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcomes in clomiphene citrate resistant infertile polycystic ovarian syndrome women after treatment with laparoscopic ovarian drilling (LOD) versus gonadotropins

Abstract: Background: Infertility is the inability of a sexually active, non-contracepting couple to achieve pregnancy in one year. Objective of present study was to compare the clinical outcome of laparoscopic ovarian drilling with gonadotropin ovulation induction in patients with clomiphene resistant Polycystic Ovarian Syndrome.Methods: Present study was a comparative interventional study conducted at the Institute of Obstetrics and Gynaecology, Sir Ganga Ram Hospital, New Delhi for a period of one and a half year. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…The two groups were matched as regard age, height, BMI, duration and type of infertility. In consistent with our results Rupa et al, (2018) enrolled sixty women between 30 and 40 years old presented with a diagnosis of anovulatory infertility due to polycystic ovarian syndrome and found that there was no enrolled significant difference in all groups in the mean age or body mass index of women participated in the study. The mean age at enrollment was 33.6 ± 4.1, and 32.4 ± 5.3 years for groups I, and II respectively (p < 0.47).…”
Section: Unilateral Versus Bilateral Laparoscopic Ovarian Drilling In...supporting
confidence: 89%
“…The two groups were matched as regard age, height, BMI, duration and type of infertility. In consistent with our results Rupa et al, (2018) enrolled sixty women between 30 and 40 years old presented with a diagnosis of anovulatory infertility due to polycystic ovarian syndrome and found that there was no enrolled significant difference in all groups in the mean age or body mass index of women participated in the study. The mean age at enrollment was 33.6 ± 4.1, and 32.4 ± 5.3 years for groups I, and II respectively (p < 0.47).…”
Section: Unilateral Versus Bilateral Laparoscopic Ovarian Drilling In...supporting
confidence: 89%